Customized chitooligosaccharide production—controlling their length via engineering of rhizobial chitin synthases and the choice of expression system - Weyer, Rita; Hellmann, Margareta J.; Hamer-Timmermann, Stefanie N.; Singh, Ratna; Moerschbacher, Bruno M. (Frontiers in Bioengineering and Biotechnology, 2022)
Chitooligosaccharides (COS) have attracted attention from industry and academia in various fields due to their diverse bioactivities. However, their conventional chemical production is environmentally unfriendly and in addition, defined and pure molecules are both scarce and expensive. A promising alternative is the in vivo synthesis of desired COS in microbial platforms with specific chitin synthases enabling a more sustainable production. Hence, we examined the whole cell factory approach with two well-established microorganisms - Escherichia coli and Corynebacterium glutamicum - to produce defined COS with the chitin synthase NodC from Rhizobium sp. GRH2. Moreover, based on an in silico model of the synthase, two amino acids potentially relevant for COS length were identified and mutated to direct the production. Experimental validation showed the influence of the expression system, the mutations, and their combination on COS length, steering the production from originally pentamers towards tetramers or hexamers, the latter virtually pure. Possible explanations are given by molecular dynamics simulations. These findings pave the way for a better understanding of chitin synthases, thus allowing a more targeted production of defined COS. This will, in turn, at first allow better research of COS’ bioactivities, and subsequently enable sustainable large-scale production of oligomers.